A Critical Analysis of the Impact of Islamization of Igembe People Through Miraa Trade in Meru County - Jotham, Kirimi Mwenda; Ataya, John Kobia; Njoroge, John Ngige (International Journal For Research In Educational Studies, 2018)
This study undertook a critical analysis of the impact of Islamization of Igembe people through miraa trade in Meru County. The research interest was provoked by the gradual and emerging prominence of Somali Muslims in the affairs of miraa business in the Igembe Region. The study was guided by objective; to critically analyse the impact of Islamization of Igembe People through miraa trade. The study drew a sample size of 383 from a target population of 126,000 miraa farmers, miraa vendors. All the thirteen-(13) miraa traders’ association officials formed part of the sample size as they were both miraa farmers and miraa vendors. The research used both quantitative and qualitative methods. The study employed descriptive study design based upon field research designed to critically analyse the impact of Islamization of the Igembe people in Meru County. Questionnaire with both structured and unstructured questions were used under a purposive sampling procedure. Data collected from the research location were analysed, summarized and interpreted using the computer software SPSS (version 22), where correlation of the variables under study determined and conclusions drawn. The partial correlation results for the study gave p-values that was significant thus showing that the independent variables are indeed related to the dependent variable making the study concrete and viable.. The study findings were, negative impacts are evident in unlawful land leasing, conflicts, boys dropping out of schools, and uncouth business practices among others. The study also recommends that the Ministry of Education to encourage boys to continue schooling instead of dropping out to join miraa businesses.